Bioactive glass and method for producing three-dimensional bioactive glass products

By adding non-ferrous metal oxides to the biologically active glass and using laser sintering and heat treatment methods, the problems of large amount of adhesive and insufficient structural strength in the selective laser sintering method in the biologically active glass in the prior art are solved, and efficient biological The molding of activated glass three-dimensional products has good biocompatibility and structural strength.

CN114516720BActive Publication Date: 2025-01-14METAL INDS RES & DEV CENT
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011295270.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-18
Publication Date
2025-01-14
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

In the selective laser sintering method, existing bioactive glasses require a large amount of adhesive due to their high melting point properties, which affects biocompatibility and molding structure strength, and holes often appear after degreasing and sintering.

Method used

By adding 1 to 10% non-ferrous metal oxides, the absorption efficiency of bioactive glass to laser energy is improved, the amount of adhesive is reduced, and laser sintering and heat treatment methods with wavelengths between 400 to 1200 nm are used to reduce the generation of holes.

Benefits of technology

It effectively reduces the amount of adhesive, improves the structural strength and biocompatibility of bioactive glass three-dimensional products, reduces the holes after high-temperature degreasing and sintering, and forms bioactive glass three-dimensional products with good biocompatibility and structural strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114516720B_ABST
    Figure CN114516720B_ABST
Patent Text Reader

Abstract

The present invention provides a bioactive glass to solve the problem that existing bioactive glass needs to be mixed with a large amount of adhesive. The bioactive glass comprises: a matrix of 60-80% by weight, a binder of 10-30% by weight, and a non-ferrous metal oxide of 1-10% by weight, wherein the non-ferrous metal oxide comprises a metal element, and the metal element can be a transition metal element selected from the group consisting of one or more of vanadium, chromium, iron, cobalt, nickel and copper. The present invention also relates to a method for manufacturing a bioactive glass three-dimensional product using the bioactive glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a bioactive glass, in particular to a bioactive glass for selective laser sintering. The present invention also relates to a method for using the bioactive glass to manufacture a bioactive glass three-dimensional product. Background Art

[0002] Bioactive glass (BAG) is a biomaterial with biocompatibility that can be dissolved in aqueous media and can connect with bone tissue and soft tissue. It is widely used in the production of dental filling materials and bone implants. The composition of existing bioactive glass includes silicon dioxide (SiO2), sodium oxide (Na2O), calcium oxide (CaO) and phosphorus pentoxide (P2O5). For example, 45S5 bioactive glass contains 45% silicon dioxide, 24.5% sodium oxide, 24.5% calcium oxide and 6% phosphorus pentoxide by weight, wherein the molar ratio of calcium element to phosphorus element is 5:1.

[0003] 3D printing, also known as additive manufacturing (AM), refers to a processing technology that uses different energy sources to melt material powder under computer control, and then stacks it layer by layer after it is melted and solidified to form a printed part. The selective laser sintering (SLS) method developed in recent years utilizes laser sintering material powders. After the low melting point binder added to the material powders is heated and melted, it is bonded with high melting point powders such as ceramics or metals, and then stacked layer by layer until the printing of the three-dimensional object is completed. It has the advantages of wide application of materials, high molding efficiency, and high material utilization rate. However, when bioactive glass is used as the material powder of the selective laser sintering method, due to its high melting point characteristics, a large amount of binder (binder) is often required to be added, such as stearic acid (stearic acid), polyvinyl alcohol (PVA), polycaprolactone (PCL), poly (lactic-co-glycolic acid), PLGA, etc. to assist in the formation of its products, and the addition amount may even be more than 50%, which not only greatly affects the biocompatibility of the formed three-dimensional object, but also requires debinding sintering at high temperature after forming into a three-dimensional object. In other words, the existing bioactive glass is not suitable as a material powder for selective laser sintering.

[0004] In view of the above, it is indeed necessary to provide a novel bioactive glass and a method for manufacturing a bioactive glass three-dimensional product using the bioactive glass. Summary of the invention

[0005] To solve the above problems, an object of the present invention is to provide a bioactive glass suitable for being formed into a three-dimensional bioactive glass product having a predetermined shape by a selective laser sintering method.

[0006] Another object of the present invention is to provide a selective laser sintering method, which uses the aforementioned bioactive glass to form a three-dimensional bioactive glass product having a predetermined shape.

[0007] The bioactive glass of the present invention may include: by weight percentage, 60-80% of a matrix, 10-30% of a binder, and 1-10% of a non-ferrous metal oxide, wherein the non-ferrous metal oxide includes a metal element.

[0008] Therefore, the bioactive glass of the present invention can greatly improve the absorption efficiency of the bioactive glass to the laser energy by adding the non-ferrous metal oxide, thereby reducing the amount of the adhesive to 10-30%. Therefore, when the bioactive glass is used as the material powder for the selective laser sintering method, the holes appearing on the formed bioactive glass three-dimensional product after degreasing and sintering can be effectively reduced, and the structural strength of the formed bioactive glass three-dimensional product can be improved, which is the effect of the present invention.

[0009] In the bioactive glass of the present invention, the metal element may be a transition metal element; for example, the transition metal element may be selected from the group consisting of one or more of vanadium, chromium, iron, cobalt, nickel and copper.

[0010] The bioactive glass of the present invention, wherein the matrix may include a silicon oxide, a sodium oxide, a calcium oxide and a phosphorus oxide; for example, the matrix includes 35-40% silicon dioxide, 5-10% sodium oxide, 39-43% calcium oxide and 10-15% phosphorus pentoxide by weight.

[0011] The method for manufacturing a three-dimensional bioactive glass product of the present invention may include: providing the bioactive glass as described above; using a laser with a wavelength between 400 and 1200 nm to laser sinter the bioactive glass to form a rough embryo; and performing a heat treatment on the rough embryo to remove the binder in the rough embryo to obtain a three-dimensional bioactive glass product.

[0012] Therefore, the method for manufacturing a three-dimensional bioactive glass product of the present invention uses the above-mentioned bioactive glass as the material powder. The radiation energy released by the laser with a wavelength between 400 and 1200 nm can be effectively absorbed by the bioactive glass, which not only improves the adhesion molding effect of the bioactive glass, but also reduces the generation of holes after high-temperature degreasing and sintering. In addition, the three-dimensional bioactive glass product molded with the bioactive glass not only has good biocompatibility but also has good structural strength, which is the effect of the present invention.

[0013] In the method for manufacturing a three-dimensional bioactive glass product of the present invention, the heat treatment can be performed on the rough blank at a temperature of 1050-1150° C. and last for 1-3 hours.

[0014] The method for producing a three-dimensional bioactive glass product of the present invention can be carried out at 1 to 3 cal / cm 2 Laser sintering is carried out at a radiation energy density of .

[0015] In the method for manufacturing a three-dimensional bioactive glass product of the present invention, the laser used for laser sintering the bioactive glass is a neodymium-doped yttrium aluminum garnet laser. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 : A flow chart of a method for manufacturing a three-dimensional bioactive glass product according to an embodiment of the present invention;

[0017] Figure 2 : Analysis results of the test pieces subjected to laser sintering at different powers and different radiation energy densities in experiment (A);

[0018] Figure 3 : Histogram of compressive strength of three-dimensional bioactive glass products of groups B1 to B3 in test (B);

[0019] Figure 4a : Results of scanning electron microscopy analysis of the bioactive glass three-dimensional article of group B1 in test (B);

[0020] Figure 4b : Results of scanning electron microscopy analysis of the bioactive glass three-dimensional article of group B2 in test (B);

[0021] Figure 4c : Results of scanning electron microscopy analysis of the bioactive glass three-dimensional article of group B3 in test (B);

[0022] Figure 5 : Histogram of cell viability test of bioactive glass three-dimensional products in groups C0 to C5 in test (C);

[0023] Figure 6 : Histogram of cell viability test of bioactive glass three-dimensional products in groups D0 to D5 in experiment (D).

[0024] Description of Reference Numerals

[0025] [the present invention]

[0026] S1: Material provision steps

[0027] S2: Laser sintering step

[0028] S3: Heat treatment step. DETAILED DESCRIPTION

[0029] In order to make the above and other purposes, features and advantages of the present invention more clearly understood, preferred embodiments of the present invention are listed below and described in detail with reference to the accompanying drawings as follows:

[0030] The bioactive glass of one embodiment of the present invention may include a substrate, a binder and a colored metal oxide in specific proportions. The bioactive glass may be used as a material powder for a selective laser sintering method, and sequentially undergo a material providing step S1, a laser sintering step S2 and a heat treatment step S3 to obtain a bioactive glass three-dimensional product having a predetermined shape.

[0031] In detail, in the sample providing step S1, the bioactive glass may include 60-80% by weight of a matrix. For example, the matrix may include oxide forms of elements such as silicon (Si), sodium (Na), calcium (Ca) and phosphorus (P). For example, the silicon oxide containing silicon may be silicon dioxide (SiO2) and silicon monoxide (SiO), etc., the sodium oxide containing sodium may be sodium oxide (Na2O), etc., the calcium oxide containing calcium may be calcium oxide (CaO), etc., and the phosphorus oxide containing phosphorus may be phosphorus (V) oxide (P2O5), phosphorus (III) oxide (P2O3) and phosphorus monoxide (PO), etc. This is understandable to those skilled in the art to which the present invention belongs and will not be elaborated herein. In this embodiment, the matrix may include 35-40% silicon dioxide, 5-10% sodium oxide, 39-43% calcium oxide, and 10-15% phosphorus pentoxide by weight.

[0032] The bioactive glass may further comprise 10 to 30% by weight of a binder, and the binder may be any binder suitable for the selective laser sintering method. For example, the binder may be stearic acid, polyvinyl alcohol (PVA), polycaprolactone (PCL), poly(lactic-co-glycolic acid), PLGA, etc., without limitation.

[0033] Furthermore, the bioactive glass further comprises 1 to 10% by weight of colored metal oxides, which are identified as non-transparent and non-white colors (i.e., various colors other than white) by the naked eye under natural light, and can reduce the transmittance of light sources of different wavelengths, thereby improving the material's absorption efficiency of light sources.

[0034] The non-ferrous metal oxide includes a metal element, and the metal element may include a transition metal element, such as vanadium (V), chromium (Cr), iron (Fe), cobalt (Co), nickel (Ni), and copper (Cu) belonging to the fourth period. For example, vanadium oxides include vanadium (II) oxide (VO), vanadium (III) oxide (V2O3), vanadium (IV) oxide (VO2), and vanadium (V) oxide (V2O5), and chromium oxides include chromium (II) oxide (CrO), chromium (III) oxide (Cr2O3), chromium (IV) oxide (CrO2), chromium (VI) oxide (CrO3), and chromium peroxide (V2O5). peroxide, etc., iron oxides include iron (II) oxide (FeO) and iron (III) oxide (Fe2O3), etc., cobalt oxides include cobalt (II) oxide (CoO) and cobalt (III) oxide (Co2O3), etc., nickel oxides include nickel (II) oxide (NiO) and nickel (III) oxide (Ni2O3), etc., copper oxides include cuprous oxide (copper (I) oxide (Cu2O), copper oxide (copper (II) oxide (CuO), copper peroxide (CuO2) and copper (III) oxide (Cu2O3), etc. In this embodiment, the staff can also mix oxides of multiple transition metal elements to serve as the non-ferrous metal oxide.

[0035] Next, in the laser sintering step S2, the worker may use a laser with a wavelength between 400 and 1200 nm, preferably, the worker may use a laser with a wavelength between 1000 and 1200 nm, to perform laser sintering on the bioactive glass, so that the bioactive glass is subjected to the radiant energy of the laser and melts to form a blank. In this embodiment, the laser may be a neodymium-doped yttrium aluminum garnet laser (Yd:YAG laser for short), which generally has an operating wavelength of about 1064 nm and can be converted to a visible light region by a nonlinear crystal, so that it can be effectively absorbed by the non-ferrous metal oxides in the bioactive glass, thereby improving the forming rate of the bioactive glass.

[0036] Furthermore, the laser may have a radiant energy density, which may be between 1 and 3 cal / cm 2 When the radiation energy density is too low, the radiation energy generated by the laser is insufficient to shape the bioactive glass into the rough blank. When the radiation energy density is too high, the formed rough blank may be burnt out.

[0037] After the bioactive glass is formed into the rough blank, the heat treatment step S3 is performed, which is to perform a heat treatment on the rough blank at a high temperature to remove the binder in the rough blank, thereby obtaining a bioactive glass three-dimensional product made of the bioactive glass. The bioactive glass three-dimensional product has good structural strength because the amount of binder used is reduced and no excess holes remain. In this embodiment, the rough blank is heat treated at a temperature of 1050-1150°C for 1-3 hours. The heat treatment duration can also be selected according to the size of the rough blank so as to remove the excess binder. At this time, the bioactive glass three-dimensional product can contain 1-10% non-ferrous metal oxide by weight, and can also contain 35-40% silicon dioxide, 5-10% sodium oxide, 39-43% calcium oxide and 10-15% phosphorus pentoxide by weight.

[0038] In order to prove that the bioactive glass can indeed be formed into the bioactive glass three-dimensional product through the selective laser sintering method, and the bioactive glass three-dimensional product has good biocompatibility and structural strength, the following tests were conducted:

[0039] (A) Adjustment of laser parameters

[0040] The test was conducted on bioactive glass containing 5% by weight of iron oxide (Fe2O3) at 1, 1.5, 2, 2.5 or 3 cal / cm 2 The radiation energy density is 3W, 4W, and 5W respectively. The results are as follows: Figure 2 As shown in the figure, although the change of power has no obvious effect on the result of laser sintering, the forming effect will be improved with the increase of radiation energy density. 2 The effect is better.

[0041] (B) Effect of heat treatment temperature on structural strength

[0042] This experiment also tested the bioactive glass containing 5% by weight of iron oxide (Fe2O3). After forming the rough blank, the rough blank was heat-treated at 1050°C (Group B1), 1100°C (Group B2), and 1150°C (Group B3) for 1 hour, and then the compressive strength of the finally obtained bioactive glass three-dimensional products was tested. The results are shown in FIG. Figure 3 As shown, the compressive strength of the three-dimensional bioactive glass product obtained by heat treatment at a temperature of 1100°C is the best, and the compressive strength of the three-dimensional bioactive glass product obtained by heat treatment at a temperature of 1050°C is the worst, which is only about 10MPa, but still meets the compressive strength of human cancellous bone (4-12MPa).

[0043] In addition, the bioactive glass three-dimensional products of groups B1 to B3 were analyzed by scanning electron microscope (SEM), and the results were as follows: Figure 4a to Figure 4c As shown, the 3D bioactive glass product of group B1 has more pores, while the 3D bioactive glass product of group B3 has larger crystal grains.

[0044] (C) Effect of iron-containing bioactive glass 3D products on cell survival

[0045] The present experiment also tested bioactive glass containing 5% by weight of iron oxide (Fe2O3). After the rough blank was formed, the rough blank was heat-treated at 1050°C (Group C3), 1100°C (Group C4), and 1150°C (Group C5) for 1 hour to obtain three-dimensional bioactive glass products of Groups C3 to C5. Zinc diethyldithiocarbamate (ZDEC), high-density polyvinyl chloride (HDPVC) and other three-dimensional bioactive glass products were prepared. The bioactive glass three-dimensional products made of high-density polyethylene (HDPE) were used as positive and negative control groups, zinc dithiocarbamate was a material known to be cytotoxic to cells, and high-density polyvinyl chloride was a material known to be non-cytotoxic to cells. The bioactive glass three-dimensional products of groups C1 to C5 were immersed in cell culture medium, reacted in a 37°C water bath for 72 hours, and then cultured the cells in the cell culture medium for 24 hours. Finally, the MTT assay (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, referred to as MTT assay) was performed to test the cell survival rate of each group of cells; and the cells of group C0 without any bioactive glass three-dimensional products were used as a comparison.

[0046] Please refer to Figure 5 As shown, the bioactive glass three-dimensional products of groups C4 and C5 subjected to heat treatment at a temperature of 1100-1150° C. do not affect the survival of cells, indicating that the bioactive glass three-dimensional products should have good biocompatibility.

[0047] (D) Effect of iron content

[0048] This experiment was conducted on bioactive glass containing 1%, 5% or 10% iron oxide (Fe2O3) by weight, and the color change, integrity and structural strength of the bioactive glass three-dimensional products were observed as evaluation criteria. The results are shown in Table 1.

[0049] Table 1. Evaluation table of bioactive glass three-dimensional products in each group of this experiment

[0050]

[0051] 1 : 0 points means no or burnt; 1 point means slight; 2 points means mild; 3 points means moderate; 4 points means severe.

[0052] 2: 0-5 points indicate no formability; 6-9 points indicate weak formability; 10-15 points indicate competent formability.

[0053] As shown in Table 1, the bioactive glass three-dimensional product of group D3 with an iron oxide addition of 5% has the best formability.

[0054] (E) Effect of copper content

[0055] This experiment was conducted on bioactive glass containing 0.5%, 1% or 2% copper oxide (CuO) by weight, and the color change, integrity and structural strength of the bioactive glass three-dimensional products were observed as evaluation criteria. The results are shown in Table 2.

[0056] Table 2. Evaluation table of bioactive glass three-dimensional products in each group of this experiment

[0057]

[0058]

[0059] 1 : 0 points means no or burnt; 1 point means slight; 2 points means mild; 3 points means moderate; 4 points means severe.

[0060] 2 : 0-5 points indicate no formability; 6-9 points indicate weak formability; 10-15 points indicate competent formability.

[0061] As shown in Table 2, the bioactive glass three-dimensional products of groups E3 and E4 with copper oxide addition of 1-2% have better formability.

[0062] (F) Effect of copper-containing bioactive glass 3D products on cell survival

[0063] The present invention also tests bioactive glass containing 0.5% (Group F3), 1% (Group F4) or 2% (Group F5) of copper oxide (CuO) by weight. After forming the rough blank, the rough blank is heat-treated at a temperature of 1050°C for 1 hour to obtain bioactive glass three-dimensional products of Groups F3 to F5. Zinc diethyldithiocarbamate (ZDEC), high-density polyvinyl chloride (HDPVC) and the like are used as the raw materials. The bioactive glass three-dimensional products made of high-density polyethylene (HDPE) were used as positive and negative control groups, zinc dithiocarbamate was a material known to be cytotoxic to cells, and high-density polyvinyl chloride was a material known to be non-cytotoxic to cells. The bioactive glass three-dimensional products of groups F1 to F5 were immersed in cell culture medium, reacted in a 37°C water bath for 72 hours, and then cultured the cells in the cell culture medium for 24 hours. Finally, the MTT test was performed to test the cell survival rate of each group of cells; in addition, the cells of group F0 without any bioactive glass three-dimensional products were used as a comparison.

[0064] Please refer to Figure 6 As shown, the bioactive glass three-dimensional products of groups F3 and F4 containing 0.5-1% copper oxide by weight do not affect the survival of cells, indicating that the bioactive glass three-dimensional products should have good biocompatibility.

[0065] In summary, the bioactive glass of the present invention reduces the amount of the binder to 10-30% by adding the non-ferrous metal oxide. Therefore, when the bioactive glass is used as a material powder for the selective laser sintering method, the holes that appear on the formed bioactive glass three-dimensional product after degreasing and sintering can be reduced, and the structural strength of the formed bioactive glass three-dimensional product can be improved, which is the effect of the present invention.

[0066] Furthermore, the method for manufacturing the three-dimensional bioactive glass product of the present invention uses the above-mentioned bioactive glass as the material powder. The radiation energy released by the laser with a wavelength between 400 and 1200 nm can be effectively absorbed by the bioactive glass, which not only improves the adhesion molding effect of the bioactive glass, but also reduces the formation of holes after high-temperature degreasing and sintering. In addition, the three-dimensional bioactive glass product molded with the bioactive glass not only has good biocompatibility, but also has good structural strength, which is the effect of the present invention.

[0067] Although the present invention has been disclosed using the above-mentioned preferred embodiments, they are not intended to limit the present invention. Any person skilled in the art may make various changes and modifications to the above-mentioned embodiments without departing from the spirit and scope of the present invention, and the technical scope protected by the present invention is still within the scope of the present invention. Therefore, the scope of protection of the present invention shall be subject to the claims.

Claims

1. A bioactive glass, characterized in that: The invention comprises: a matrix of 60-80% by weight, a binder of 10-30% by weight, and 5% by weight of ferric oxide. The matrix comprises 35-40% by weight of silicon dioxide, 5-10% by weight of sodium oxide, 39-43% by weight of calcium oxide, and 10-15% by weight of phosphorus pentoxide.

2. A bioactive glass, characterized in that: The invention comprises: a matrix of 60-80% by weight, a binder of 10-30% by weight and copper oxide of 1-2% by weight, wherein the matrix comprises silicon dioxide of 35-40% by weight, sodium oxide of 5-10% by weight, calcium oxide of 39-43% by weight and phosphorus pentoxide of 10-15% by weight.

3. A method for manufacturing a three-dimensional bioactive glass product, characterized in that: include: Providing a bioactive glass as described in any one of claims 1 or 2; Using a laser with a wavelength between 400 nm and 1200 nm, laser sintering the bioactive glass to form a rough blank; and The rough blank is subjected to a heat treatment to remove the binder in the rough blank to obtain a three-dimensional bioactive glass product.

4. The method for manufacturing a three-dimensional bioactive glass product according to claim 3, wherein: The heat treatment is performed on the rough blank at a temperature of 1050-1150° C. for 1-3 hours.

5. The method for manufacturing a three-dimensional bioactive glass product according to claim 3, wherein: 1~3cal / cm 2 Laser sintering is carried out at a radiation energy density of .

6. The method for manufacturing a three-dimensional bioactive glass product according to claim 3, wherein: The laser used for laser sintering the bioactive glass is a neodymium-doped yttrium aluminum garnet laser.

Citation Information

Patent Citations

  • Degradable porous glass rack having bioactivity and preparation method

    CN1562834A

  • Method for forming an organic light emitting diode device

    US20100304513A1